2, 3′, 4, 4′, 5-Pentachlorobiphenyl Induced Thyrocyte Autophagy by Promoting Calcium Influx via Store-Operated Ca2+ Entry. (16th July 2020) - Wang, Li; Xu, Wenli; Zhou, Qi; Xu, Bojin; Sheng, Yunlu; Sun, Minne; Chen, Huanhuan; Wang, Yucheng; Ding, Guoxian; Duan, Yu
Abstract: PCB118, a 2, 3′, 4, 4′, 5-pentachlorobiphenyl, has been shown to destroy thyroidal ultrastructure and induce thyrocyte autophagy. Previously, we reported that PCB118 promoted autophagosome formation in vivo and in vitro, but more details remain to be revealed. To explore the underlying mechanism by which PCB118 regulates thyrocyte autophagy, Fischer rat thyroid cell line-5 (FRTL-5) cells were exposed to different doses of PCB118 at 0, 0.25, 2.5, and 25 nM for 0–48 h. Western blot analysis of autophagy-related proteins P62, BECLIN1, and LC3 demonstrated that PCB118 induced autophagy formation in dose- and time-dependent manner. Moreover, laser scanning confocal microscopy and flow cytometry showed PCB118 treatment led to time- and dose-dependent increase in intracellular calcium concentration ([Ca 2+ ]i ). Additionally, PCB118 promoted store-operated Ca 2+ entry (SOCE) channel followed by significant increase of ORAI1 and STIM1 protein levels. On the other hand, PCB118 induced thyroidal autophagy via class III β‐tubulin (TUBB3)/death-associated protein kinase 2 (DAPK2)/myosin regulatory light chain (MRLC)/autophagy-related 9A (ATG9A) pathway in FRTL-5 cells. Pretreatment with SOCE inhibitor SKF96365 reduced cytosolic Ca 2+, ORAI1, STIM1, and BECLIN1 levels as well as LC3 II/LC3 I ratio, while increased P62 expression. SKF96365 also inhibited TUBB3/DAPK2/MRLC/ATG9A pathway in FRTL-5 cells treated by PCB118. Our results provide evidence that PCB118 may induce thyroidal autophagy through TUBB3-related signaling pathway, and these effects are likely to be regulated by calcium influx via SOCE channel.